Analysis of the Performance of the Indonesian National Education System in Achieving Global Education Targets - susanty, septy (PT. Anagata Sembagi Education, 2024)
This article analyzes the performance of Indonesia's national education system in its efforts to achieve global education targets, particularly those set by the 2030 Education Agenda and the Sustainable Development Goals (SDGs). This study uses a qualitative approach with secondary data analysis methods that include government policy reports, international survey results, and case studies from various regions in Indonesia. The main focus of the study covers three important aspects: accessibility of education, quality of education, and equity of education. The findings show that although Indonesia has made progress in increasing access to basic education, significant challenges remain in terms of quality of education and equity, especially at the secondary and tertiary levels. The analysis also identifies several policies that have been implemented, such as inclusive education programs and improving teacher quality, but the results have not fully met global targets. This article provides strategic recommendations for policymakers, educators, and other stakeholders to improve the effectiveness of the education system and achieve the set global targets.